7 - Decolonization and Popular Contestation in Sierra Leone: The Peasant War of 1955-1956 - Ismail O. D. Rashid (Afrika Zamani, 2022)
Between 1955 and 1956, peasants in the northern region of Sierra Leone, following the steps of workers in Freetown, launched an insurrection to protest colonial taxation and the exploitative practices of their paramount chiefs and local ruling elite. The insurrection, which started as a protest against the paramount chief of Port Loko, Alkali Modu, soon engulfed all of the districts in the northern region and parts of the southern region. Through their violent actions, the peasants indicated that the oppressive practices and the excessive financial demands by the paramount chiefs and the state were neither tenable nor acceptable during the decolonization era. Their actions also illustrated the inadequacy of ‘traditional’ and ‘paternalistic’ forms of governance that had been the linchpin of British colonialism in Sierra Leone, and which still underpinned the chieftaincy and new local institutions that had been created by the departing British. The peasant insurrection interrupted the tranquil process of decolonization being executed between the Sierra Leonean elite and the British, and it took a heavy toll on the national and local security forces. However, the subsequent public investigation and acknowledgement of the peasant grievances by the Cox Commission of Inquiry as well as the restitutive actions by the SLPP government affirmed the legitimacy of many of the peasant claims. With the 1955-56 insurrection, it could be argued that the peasants in northern Sierra Leone had not only rudely interrupted the process of decolonization, they had forcib y renegotiated the terms of a ‘new’ Sierra Leone political order in their favour.